2013
DOI: 10.1128/genomea.00217-13
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Myxococcus xanthus Wild-Type Strain DZ2, a Model Organism for Predation and Development

Abstract: Myxococcus xanthus is a member of the Myxococcales order within the Deltaproteobacteria subdivision. The myxobacteria reside in soil, have relatively large genomes, and display complex life cycles. Here, we report the whole-genome shotgun sequence of strain DZ2, which includes unique genes not found previously in strain DK1622.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…5). The third strain, DZ2, shares a common ancestor with DK1622 but was stored independently by the Zusman lab (20,21). When any of these ancestral strains was mixed with a DK1622-derived strain, the former strains readily outcompeted the latter strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5). The third strain, DZ2, shares a common ancestor with DK1622 but was stored independently by the Zusman lab (20,21). When any of these ancestral strains was mixed with a DK1622-derived strain, the former strains readily outcompeted the latter strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the origin of currently used M. xanthus laboratory strains is murky, Wu and colleagues (45) indicated that the Beebe strain was transferred to UC Berkeley, where it was maintained in Roger Stanier's strain collection. Both FB and DZ2 were obtained from the Berkeley collection (20,21,46). The claim by Wu et al is supported by the fact that ATCC strains 19368 and 25232 are cross-listed in the ATCC database.…”
Section: Discussionmentioning
confidence: 99%
“…M. xanthus DK 1622, apart from Anaeromyxobacter dehalogenans 2CP-C, was the first to have its genome sequenced. Further, different myxobacterial genomes have been completely sequenced: Sorangium cellulosum So ce56 and Stigmatella aurantiaca DW 4/3-1, Haliangium ochraceum, Myxococcus fulvus, Corallococcus coralloides, Myxococcus stipitatus, Cystobacter violaceus (Li et al 2011;Huntley et al 2012Huntley et al , 2013Muller et al 2013;Stevens et al 2014). Most myxobacteria are composed of a single circular chromosome, and no extra-chromosomal plasmids were known until 1980, when the first endogenous plasmid was identified in Myxococcus fulvus.…”
Section: Genomementioning
confidence: 99%
“…When cells sense low nutrient availability, they begin a developmental program that results in multicellular fruiting-body formation and differentiation into resistant myxospores (18). Regulation of these complex processes is governed in part by a large repertoire of signaling proteins, including 127 TCS and 8 chemosensory systems (15,16). In this report, we characterize the Che7 ACF chemosensory system for its role in M. xanthus development.…”
mentioning
confidence: 99%
“…The soil bacterium Myxococcus xanthus has over 40 SD-RRs, 6 of which are genetically associated with chemosensory systems (15,16). M. xanthus is a model organism for the study of signal transduction and development.…”
mentioning
confidence: 99%